2021
DOI: 10.3389/fnut.2021.761978
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Gut Microbiota in the Development of Psoriasis Vulgaris

Abstract: Objectives: Psoriasis is a common chronic recurrent dermatitis. Accumulating observations show gut microbiota dysbiosis in psoriasis. We intend to further investigate the relationship between intestinal microbiota and psoriasis development.Design: We first performed an epidemiological investigation on differences of gastrointestinal discomfort symptoms between patients with psoriasis and general population. Then variation of gut microbiota in patients with psoriasis (un)treated with acitretin plus narrow-band … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…In patients with psoriatic arthritis, there was a decrease in the abundance of certain bacteria such as Akkermansia, Ruminococcus, Pseudobotyrivibrio, Paraacteroides, Alistipes, and Coprococcus [14,16,32]. In patients with psoriasis vulgaris showed changes in the proportions of Firmicutes and Bacteroides, and a decrease in the abundance of Actinomyces, Vitallis, and Coprococcus [11,14,33]. However, the conclusions of various studies are not consistently the same.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with psoriatic arthritis, there was a decrease in the abundance of certain bacteria such as Akkermansia, Ruminococcus, Pseudobotyrivibrio, Paraacteroides, Alistipes, and Coprococcus [14,16,32]. In patients with psoriasis vulgaris showed changes in the proportions of Firmicutes and Bacteroides, and a decrease in the abundance of Actinomyces, Vitallis, and Coprococcus [11,14,33]. However, the conclusions of various studies are not consistently the same.…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidence has shown that the pathogenesis of psoriasis is related to the disorder of gut microbiota. The number, abundance and proportion of gut microbiota in patients with psoriasis are significantly changed 40,41 . The disorder of gut microbiota may induce the activation of systemic inflammation by affecting the function of immune cells and the secretion of cytokines, and affect the development of psoriasis 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The number, abundance and proportion of gut microbiota in patients with psoriasis are significantly changed. 40 , 41 The disorder of gut microbiota may induce the activation of systemic inflammation by affecting the function of immune cells and the secretion of cytokines, and affect the development of psoriasis. 42 In addition to immune‐inflammatory pathways, the involvement of gut microbiota disorders in the pathogenesis of psoriasis may be related to the following factors: (1) Intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 Turicibacter as a potential pathobiont and its interaction with the host are poorly understood, and thus its basic pathogenic mechanisms need to be further investigated. Coprococcus 1 belongs to the Lachnospiraceae family and can produce SCFAs 36 . SCFAs are the fundamental gut microbial byproducts that are related to microbiome-gut-brain axis function.…”
Section: Discussionmentioning
confidence: 99%